Hydrostatin-SN10 Ameliorates Pancreatitis-Induced Lung Injury by Affecting IL-6-Induced JAK2/STAT3-Associated Inflammation and Oxidative Stress. (18th November 2019) - Piao, Xuehua; Zou, Yanping; Sui, Xiaodan; Liu, Baohai; Meng, Fanji; Li, Shuangdi; Zhang, Qingyu; Ma, Chi; Wu, Tong
Abstract : Hydrostatin-SN1 (peptide sequence, DEQHLETELHTLTSVLTANGFQ), a kind of peptides extracted from snake venom, has been reported to have anti-inflammatory effect, but its truncated mutant hydrostatin-SN10 (peptide sequence, DEQHLETELH) on pancreatitis-induced acute lung injury has not been well documented. Interleukin- (IL-) 6-induced Janus Kinase 2/Signal Transducer and Activator of Transcription 3 (JAK2/STAT3) pathway is involved with inflammatory and oxidative stress activities and may be associated with the pathogenesis of lung injury, and related molecules were measured. Taurocholate-induced pancreatitis associated with acute lung injury was established and treated with hydrostatin-SN10. Pancreatitis was confirmed by measuring the serum levels of amylase, lipase, and trypsinogen and urinary amylase. Lung injury was determined by histologically assessing acinar cell changes. The related molecules of IL-6-induced JAK2/STAT3-associated inflammation and oxidative stress were quantitated by real time-PCR, Western blot, and/or immunochemical assay. Hydrostatin-SN10 reduced the levels of serum amylase, lipase, and trypsinogen and urinary amylase when compared with the model group (p < 0.05 ). Hydrostatin-SN10 significantly inhibited the IL-6-stimulated JAK2/STAT3 pathway and reduced the number of apoptotic cells via the downregulation of caspase 3 and BAX (proapoptotic) and upregulation of Bcl2 (antiapoptotic) (p < 0.05 ). IL-6 induced the increase in the levels of JAK2 and STAT3, which was reversed by hydrostatin-SN10 treatment (p < 0.05 ). In addition, hydrostatin-SN10 reduced the expression of IL-6 and TNF- (tumor necrosis factor-) α and increased the level of IL-10 (p < 0.05 ). On the other hand, hydrostatin-SN10 treatment increased the levels of superoxide dismutase (SOD) and reduced glutathione (GSH) and the levels of malondialdehyde (MDA) and alanine aminotransferase (ALT) (p < 0.05 ). These results suggest that hydrostatin-SN10 may inhibit pancreatitis-induced acute lung injury by affecting IL-6-mediated JAK2/STAT3 pathway-associated inflammation and oxidative stress.